CFD analysis of exothermic reactions in Al-Au nano multi-layered foils - Raić, Karlo (Materiali in tehnologije, 2011)
This work presents the possibility of numerical modelling using Computational Fluid Dynamics (CFD) in the field of nano-foils. The governing equations were solved using a Finite Volume Methodology (FVM). The computational domain was discretized using a uniform Cartesian grid with the appropriate mesh size along the x and y directions employing the corresponding number of grid points. The field variables were discretized at the cell centres and the spatial, as well as the time, derivatives were approximated using the second-order accurate numerical scheme. The time-evolution of the temperature and concentration fields, as well as the atomic diffusion coefficient, will be presented for the appropriate Al-Au nano-foil geometry and boundary conditions.
Keywords: nanofolije; aluminij; Aluminij Mostar; aluminum; zlato; finite element method; metoda končnih elementov; prenos toplote; prenos snovi